Hubungan antara Pola Makan dengan Kadar Asam Urat pada Lansia di Posyandu Lansia Srikandi Kecamatan Lowokwaru Kota Malang - Gresela Rambu Kaleka Mali, Aquina; Erni Yohani Mahtuti; Faisal Faisal; Evi Dwi Prastiwi (ABDIMAS TERAPAN : Jurnal Pengabdian Kepada Masyarakat Terapan, 2024)
Gout, commonly known as Gout Arthritis, is a disease characterized by sudden, recurrent and painful attacks. Broadly speaking, purines are obtained from food, if the diet is not changed, excessive levels of uric acid in the blood will cause uric acid crystals to accumulate, if crystals form in the joint fluid, there will be a severe and sudden pain attack. This study aims to determine the relationship between diet and uric acid levels in the elderly at the Srikandi Elderly Posyandu, Lowokwaru District, Malang City. This type of research is qualitative using a cross sectional research design. The population was all elderly people aged 40-50 years, 51-60 years, 61-75 years, and 91 years at the Srikandi Elderly Posyandu, Lowokwaru District, Malang City, totaling 50 respondents. The sampling technique used purposive sampling with a sample of 35 respondents. Data collection using questionnaires and capillary blood sampling in the elderly. Tested using spearman rank analysis. The results showed that there was a relationship between diet and uric acid levels in the elderly (p-Value = 0.114). The conclusion is that there is a relationship between diet and uric acid levels in the elderly at the Srikandi Elderly Posyandu, Lowokwaru District, Malang City. It is recommended to the community in the work environment of the Srikandi Elderly Posyandu, Lowokwaru District, Malang City to maintain a good diet so that uric acid levels remain normal.